biolsciences 2022
DOI: 10.55006/biolsciences.2022.2105
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on pharmacological activities of Withania somnifera

Abstract: Withania somnifera, is a well-known medicinal herb in the Solanaceae family that has been used for over 3,000 years all over the world. It's also known as "Indian ginseng" and winter cherry, and it's an Ayurvedic and indigenous medicine. The fragrance is described by the word "Withania somnifera", which means "horse." In India, the Middle East, and portions of Africa, it is grown. Isopellertierine, anferine, withanolides, withaferins, and withanolides are the main components of Withania somnifera. It has the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is an important medicinal plant found across the Indian subcontinent that has been widely used in Ayurvedic and traditional systems for over 3,000 years [16]. Withania somnifera has been reported to have anti-in ammatory, anti-arthritic, analgesic, hepatoprotective, anti-epileptic, anti-cancer, anti-Alzheimer, cardioprotective, antiparkinson, neuroprotective, anti-fungal, anti-microbial, anti-diabetic, properties [17]. The majority of Withania somnifera's biological activities have been associated withaferin-A and withanolide-A.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important medicinal plant found across the Indian subcontinent that has been widely used in Ayurvedic and traditional systems for over 3,000 years [16]. Withania somnifera has been reported to have anti-in ammatory, anti-arthritic, analgesic, hepatoprotective, anti-epileptic, anti-cancer, anti-Alzheimer, cardioprotective, antiparkinson, neuroprotective, anti-fungal, anti-microbial, anti-diabetic, properties [17]. The majority of Withania somnifera's biological activities have been associated withaferin-A and withanolide-A.…”
Section: Introductionmentioning
confidence: 99%
“…Various pharmacological activities have been reported in W. somnifera , including anti-inflammatory, analgesic, anti-arthritic, hepatoprotective, anti-cancer, anti-epileptic, anti-Alzheimer, antiparkinson, cardioprotective, neuroprotective, anti-microbial, anti-fungal, anti-oxidant, immunomodulatory, anti-depressant, anti-diabetic, anti-platelet, fibrinolytic, etc. ( Ku et al, 2014 ; Kumar et al, 2015 ; Paul et al, 2021 ; Parihar, 2022a ). The major bioactive compounds reported in W. somnifera are the steroidal lactones called withanolides, the most important ones that are responsible for various bioefficacies are withaferin-A, withanolide-D, and withanone ( Saleem et al, 2020 ; Paul et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various insilico studies have shown that bioactive compounds present in the plant have been shown to target a few enzymes and the main spike protein of the virus via which it attaches with the host ACE2 receptor and enters the cell ( Parihar, 2022a ). Withanoside and Somniferine have been shown by molecular docking and dynamic stimulation to exhibit a high binding affinity for SARS-CoV-2 main protease enzyme (Mpro) with high binding affinity and have therapeutic potential against COVID-19 ( Shree et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%